ADPF: Instrumentos de defesa dos preceitos constitucionais fundamentais - Bernardina, Alexandre Caiado Ribeiro Dalla (2006)
The present work addresses the Challenge based on default of Fundamental Precept (ADPF) pursuant to article 102, first paragraph of the 1988 Federal Constitution of the Federative Republic of Brazil and regulated by Law 9,822/99. The main goal of this research is to analyze the object of the ADPF and the right of action pursuant to Law 9,822/99. The scientific method used is characterized by a dialectic approach and by the use of bibliographical and documental research techniques. The theoretical reference is the doctrine of Hans Kelsen and its postulates. Concepts of the Theory of Law, concepts of Constitutional Law and foreign statutes that have inspired the Brazilian Lawmaker in the regulation of the ADPF will be analyzed. The lack of knowledge in the legal community and the current case law, including in the Brazilian Supreme Court, as to the basic concepts of the ADPF and its conjecture belittle the relevance of such constitutional remedy. This research demonstrates the need for a review of the current prevailing concepts among the national legal community regarding the means of impugnation and the conjecture of the ADPF in order to safeguard the effective use of such action as the main instrument of defense of the fundamental constitutional precepts.